2021
DOI: 10.1186/s12913-021-06242-5
|View full text |Cite
|
Sign up to set email alerts
|

Importance of support groups to the health and well-being of vulnerable children and young people living with HIV: a case study of the Kids Clubs program in Haiti

Abstract: Background Although access to antiretroviral therapy (ART) among children and young people living with HIV has increased in recent years, adherence to medication and viral suppression remain challenges. Evidence of benefits of support groups is growing and reflects a range of models and approaches. Since 2014, hospital-linked psychosocial support groups for children and young people living with HIV, known as Kids Clubs, have been established throughout Haiti. The program provides safe spaces fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Consistent with existing literature, a study conducted in Mpumalanga on community-based adherence clubs indicated they played a crucial role in reducing overcrowding in healthcare facilities, defaulter rates, improving treatment adherence, and reducing stigma and discrimination [74]. These results are similar to those reported in the study conducted in Haiti whereby the Kids Club program assisted caregivers and children living with HIV with psychosocial development and well-being through group interaction [75].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with existing literature, a study conducted in Mpumalanga on community-based adherence clubs indicated they played a crucial role in reducing overcrowding in healthcare facilities, defaulter rates, improving treatment adherence, and reducing stigma and discrimination [74]. These results are similar to those reported in the study conducted in Haiti whereby the Kids Club program assisted caregivers and children living with HIV with psychosocial development and well-being through group interaction [75].…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that the Kids Club program was crucial in giving orphaned children the educational opportunities they needed to overcome their shyness, boost their self-esteem, give them encouragement and hope, and bring pleasure into their lives. Individuals who disclosed to the club that they were HIVpositive discussed how being a part of it had improved their knowledge of the virus, their ability to maintain their health, and their outlook on life [75]. Moreover, caregivers also reported how treatment treatment-taking behavior of orphaned children who attended the Kids Club improved.…”
Section: Discussionmentioning
confidence: 99%
“…The support groups likely prepare the adolescents and youth to counter some stigmatizing situations and bolster their confidence and sense of self-worth leveraging peer support. Expanding the reach of youth responsive clinics and peer support groups, which are highly advocated for to enhance HIV treatment outcomes [ 77 79 ], could be effective ways to mitigate internalized stigma for youth.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been demonstrated in a study by Settergren et al, on the importance of support groups amongst children living with HIV in Haiti. 24 This feeling of well-being is a shared benefit between the asthma patient and the parent/caregiver. A report from one of our parent key informants that she now encourages her son to take his medication suggests that better understanding may influence parents' enthusiasm to support or seek adequate care.…”
Section: Discussionmentioning
confidence: 99%